2014
DOI: 10.1177/2319510x14529490
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Factors Influencing the Intention to Adopt RFID Technology in Retail Industry: An Empirical Study

Abstract: Today, radio frequency identification (RFID) technology is considered as a paramount tool in boosting the competitiveness of supply chain firms. There is an overall consensus regarding the remarkable influence of RFID upon the productivity level of firms. The realisation of such influences will only be tangible if, and when, RFID’s systems are extensively spread and used in the supply chain. It is crucial to realise the determinants of RFID adoption intention among the firms. There exists several reviews withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 51 publications
0
10
0
1
Order By: Relevance
“…Sharma et al [76] stated that trading partners' pressure is one of the dominant factors affecting innovation adoption. Firms might adopt specific innovation if pressure comes from powerful partners who mostly contribute to their profitability [77]. To and Ngai [78] found that a firm adopts innovation if dominant suppliers have already adopted that technology earlier.…”
Section: Competitor Trading Partner and Customer Pressurementioning
confidence: 99%
See 3 more Smart Citations
“…Sharma et al [76] stated that trading partners' pressure is one of the dominant factors affecting innovation adoption. Firms might adopt specific innovation if pressure comes from powerful partners who mostly contribute to their profitability [77]. To and Ngai [78] found that a firm adopts innovation if dominant suppliers have already adopted that technology earlier.…”
Section: Competitor Trading Partner and Customer Pressurementioning
confidence: 99%
“…External support is considered the support that comes from outside the firm, and it influences the firms' decision-making process, precisely, when the company accepts new technology [77]. Wu and Subramaniam [85] stated that the greater possibility of accepting new technology happens when support comes from an external body.…”
Section: External Supportmentioning
confidence: 99%
See 2 more Smart Citations
“…The incorporation of Retail 4.0 technologies in Malaysia is rather slow (Hasbullah, 2018) when compared to the United States (Mukherjee et al, 2018), China (Li et al, 2018) and many of the countries in Europe (Bertacchini et al, 2017;Trotter, 2017). This is mainly due to the high cost (Saremi & Taghizadeh, 2013;Padyar, Endut, Yahya, & Abdull Rahman, 2014) and complexity (Paydar, Endut, Yahya, & Abdull Rahman, 2014) associated with these technologies. However, there is sufficient evidence to show that these technologies have already reached Malaysian shores, albeit on a smaller scale.…”
mentioning
confidence: 99%